Gamification- and Virtual Reality-Based Learning Environment for UML Class Diagram Modeling - Yigitbas, Enes; Schmidt, Maximilian; Bucchiarone, Antonio; Bassanelli, Simone; Engels, Gregor (IEEE Global Engineering Education Conference 2024)

Métodos de la mediación de cultura en el entrenamiento práctico de futuros/as profesores/as de Alemán como Lengua Extranjera - Treder, Alexandra (Revista Lengua y Cultura)
This study investigates the teaching methods that future teachers of German as a foreign language use in cultural mediation. Utilizing a qualitative and hermeneutic approach, it analyzes data from a teacher-training module of the International Master's in German as a Foreign/Second Language that Friedrich Schiller University Jena in Germany offers. Participants taught an online course to students from a Japanese university, which focused on cultural learning. Within the teacher training module, the participants discussed their lesson plans, conducted classes, and subsequently reflected on their teaching practices by exploring and critiquing the practical application of their teaching skills. The analysis, which was conducted using qualitative evaluative content analysis following Kuckartz's (2018) approach, revealed a preference for distributive/instructive methods, with some recognition of interactive and collaborative methods. A tendency towards both repetitive and reflective practices was evident, with a predominant focus on content that was specific to a supposed target culture rather than intercultural or transcultural content. The study highlights the need to balance knowledge transmission with the development of critical and reflective skills in cultural mediation. It emphasizes the importance of incorporating collaborative and interactive methods, which promote a critical attitude that is necessary in language teachers and learners. In conclusion, this study advocates adaptive and reflective teaching as an essential component in the training of future language teachers in globalized contexts.
Keywords: cultural mediation; teacher training; foreign language teaching; teaching methods; teaching practice

Common pitfalls to avoid while using multiobjective optimization in machine learning - Akhter, Junaid; Fährmann, Paul David; Sonntag, Konstantin; Peitz, Sebastian (arXiv)

Detecting Security-Relevant Methods using Multi-label Machine Learning - Johnson, Oshando; Piskachev, Goran; Krishnamurthy, Ranjith; Bodden, Eric (Proceedings of the 46th International Conference on Software Engineering, IDE Workshop)
To detect security vulnerabilities, static analysis tools need to be configured with security-relevant methods. Current approaches can automatically identify such methods using binary relevance machine learning approaches. However, they ignore dependencies among security-relevant methods, over-generalize and perform poorly in practice. Additionally, users have to nevertheless manually configure static analysis tools using the detected methods. Based on feedback from users and our observations, the excessive manual steps can often be tedious, error-prone and counter-intuitive. In this paper, we present Dev-Assist, an IntelliJ IDEA plugin that detects security-relevant methods using a multi-label machine learning approach that considers dependencies among labels. The plugin can automatically generate configurations for static analysis tools, run the static analysis, and show the results in IntelliJ IDEA. Our experiments reveal that Dev-Assist's machine learning approach has a higher F1-Measure than related approaches. Moreover, the plugin reduces and simplifies the manual effort required when configuring and using static analysis tools.

The meaning landscape of the concept of the total derivative in multivariable real analysis textbooks: an analysis based on a new model of meaning - Lankeit, Elisa; Biehler, Rolf (ZDM – Mathematics Education)
Abstract In this paper, we propose a novel conceptual framework tailored for modeling the meaning of mathematical concepts in university-level mathematics, addressing their rigorous nature and their relationships with related concepts as well as interpretations in various contexts. Within this framework, we present a model of meaning for the concepts of total differentiability and total derivative that provides a variety of possible interpretations and aspects. We then use the proposed model of meaning as a tool for analyzing three different textbooks for mathematics majors on the topic of multidimensional differentiability. ﻿Our paper is an example of a subject matter analysis of a topic in university mathematics carried out in a structured way. The model of meaning for total differentiability presented in this paper could inspire course design and analysis including the design of assignments and assessments for students. Moreover, it could serve as a valuable research tool for further analyses. For example, it could be used as a framework for analyzing courses taught or as a basis for developing a test instrument to assess students’ understanding. With our textbook analysis, we begin to examine the landscape of textbooks regarding differentiability concepts in the multidimensional case, shedding light on the diversity of meaning facets that are covered in the textbooks. These results could be useful for guiding instructors and learners in selecting and using textbooks for teaching and learning based on their respective needs.

A mixed‐methods study of the quality of parental support during adolescents' information‐related Internet use as a co‐construction process - Kurock, Ricarda; Teichert, Jeannine; Meister, Dorothee M.; Gerhardts, Lara; Buhl, Heike M.; Bonanati, Sabrina (Journal of Adolescence)
Abstract Introduction In Europe, most Internet searches for school‐related tasks are situated at home, where parents can support adolescents. Although the frequency (quantity) of parental support has already been analyzed, a research gap exists concerning the quality of parental support in adolescents' information‐related Internet use. The quality of parental support in the field of homework involvement is known to be a predictor of adolescents' learning motivation and academic achievement, often discussed with regard to self‐determination theory (SDT) in terms of autonomy support, structure, emotional support, and control. These categories were adapted in this study to analyze parents' support in adolescents' Internet searching activities. Methods Using a mixed‐methods approach, we combined quantitative questionnaires and qualitative observations to analyze joint information‐related Internet uses. Therefore, 243 parent–adolescent dyads were surveyed and six parent–adolescent dyads were observed by videography in 2019/2020 in Germany. The adolescents were 11 years old, on average. Results The parents rated all qualities higher than the adolescents. Emotional support was rated highest by both groups, whereas structure was rated lowest. Adolescents' and parents' view on parental support differ. The qualitative study revealed parents' often interfering behavior, whereas emotional support was low. Further, the active role of adolescents was highlighted in both quantitative and qualitative data. Conclusions By combining quantitative and qualitative approaches, we demonstrated a fruitful application of SDT in analyzing the quality of parental support during adolescents' Internet searches at home and shed light on the co‐construction of joint Internet searches.
Keywords: Psychiatry and Mental health; Developmental and Educational Psychology; Social Psychology; Pediatrics; Perinatology and Child Health

Experimentally Verified 22 kW, 30 kHz LLC Resonant Converter Design with new Control for a 1 MW Cascaded H-Bridge Converter - Unruh, Roland; Böcker, Joachim; Schafmeister, Frank (ECCE Europe 2024; IEEE Energy Conversion Congress & Exposition Europe)

The acute effect of a β-glucan-enriched oat bread on gastric emptying, GLP-1 response, and postprandial glycaemia and insulinemia: a randomised crossover trial in healthy adults - Revheim, Ingrid; Ballance, Simon; Standal, Adelheid Fretland; Rieder, Anne; Dierkes, Jutta; Buyken, Anette; Gilja, Odd Helge; Hausken, Trygve; Rosendahl-Riise, Hanne (Nutrition & Metabolism)
Abstract Background The cereal fibre β-glucan reduces postprandial glycaemia, however, the underlying mechanisms are not fully understood. Thus, the aim of this study was to investigate the acute effect of a β-glucan-enriched oat bread on gastric emptying half-time ( T 1/2 ), gastric emptying lag phase ( T lag ), and gastric emptying rate (GER), and the secretion of glucagon-like peptide-1 (GLP-1) as potential means to influence postprandial glycaemia. Methods A randomised crossover trial was conducted in 22 healthy adults (age 24.6 ± 3.1 years, BMI 23.1 ± 2.7 kg/m 2 ) receiving 25 g available carbohydrates from a β-glucan-enriched oat bread or a control whole-wheat bread at two non-consecutive days. T 1/2 , T lag , and GER were determined based on ultrasound measures of the cross-sectional gastric antrum area in the fasting state and 15, 30, 45, 60, 90, and 120 min postprandially. Capillary glucose, serum insulin, and plasma GLP-1 concentrations were measured at the same time points. Results A biphasic pattern of gastric emptying with a distinct T lag before the commencement of emptying was observed in most subjects for both bread types. While no differences in GER were evident ( p = 0.562), consumption of the oat bread significantly increased T 1/2 by 18 min and T lag by 14 min compared with the whole-wheat bread ( p = 0.005 and p = 0.010, respectively). In addition, the oat bread significantly reduced iAUC 2h for glucose and insulin responses compared with the whole-wheat bread ( p = 0.001 and p < 0.001, respectively). There were no significant differences in GLP-1 response between the two breads ( p = 0.892). Conclusion The increased T 1/2 and T lag could offer a potential mechanism for the observed attenuation of postprandial glycaemia and insulinemia after consumption of the β-glucan-enriched oat bread compared with the whole-wheat bread. Trial registration : The study is registered at clinicaltrails.gov (NCT04571866).

Protein intake and cancer: an umbrella review of systematic reviews for the evidence-based guideline of the German Nutrition Society - Kühn, Tilman; Kalotai, Nicole; Amini, Anna M.; Haardt, Julia; Lehmann, Andreas; Schmidt, Annemarie; Buyken, Anette; Egert, Sarah; Ellinger, Sabine; Kroke, Anja; Lorkowski, Stefan; Louis, Sandrine; et al. (European Journal of Nutrition)
Abstract Purpose It has been proposed that a higher habitual protein intake may increase cancer risk, possibly via upregulated insulin-like growth factor signalling. Since a systematic evaluation of human studies on protein intake and cancer risk based on a standardised assessment of systematic reviews (SRs) is lacking, we carried out an umbrella review of SRs on protein intake in relation to risks of different types of cancer. Methods Following a pre-specified protocol (PROSPERO: CRD42018082395), we retrieved SRs on protein intake and cancer risk published before January 22th 2024, and assessed the methodological quality and outcome-specific certainty of the evidence using a modified version of AMSTAR 2 and NutriGrade, respectively. The overall certainty of evidence was rated according to predefined criteria. Results Ten SRs were identified, of which eight included meta-analyses. Higher total protein intake was not associated with risks of breast, prostate, colorectal, ovarian, or pancreatic cancer incidence. The methodological quality of the included SRs ranged from critically low (kidney cancer), low (pancreatic, ovarian and prostate cancer) and moderate (breast and prostate cancer) to high (colorectal cancer). The outcome-specific certainty of the evidence underlying the reported findings on protein intake and cancer risk ranged from very low (pancreatic, ovarian and prostate cancer) to low (colorectal, ovarian, prostate, and breast cancer). Animal and plant protein intakes were not associated with cancer risks either at a low (breast and prostate cancer) or very low (pancreatic and prostate cancer) outcome-specific certainty of the evidence. Overall, the evidence for the lack of an association between protein intake and (i) colorectal cancer risk and (ii) breast cancer risk was rated as possible . By contrast, the evidence underlying the other reported results was rated as insufficient . Conclusion The present findings suggest that higher total protein intake may not be associated with the risk of colorectal and breast cancer, while conclusions on protein intake in relation to risks of other types of cancer are restricted due to insufficient evidence.

Dietary protein and blood pressure: an umbrella review of systematic reviews and evaluation of the evidence - Boeing, Heiner; Amini, Anna M.; Haardt, Julia; Schmidt, Annemarie; Bischoff-Ferrari, Heike A.; Buyken, Anette; Egert, Sarah; Ellinger, Sabine; Kroke, Anja; Lorkowski, Stefan; Louis, Sandrine; Nimptsch, Katharina; et al. (European Journal of Nutrition)
Abstract Introduction This umbrella review aimed to investigate the evidence of an effect of dietary intake of total protein, animal and plant protein on blood pressure (BP), and hypertension (PROSPERO: CRD42018082395). Methods PubMed, Embase and Cochrane Database were systematically searched for systematic reviews (SRs) of prospective studies with or without meta-analysis published between 05/2007 and 10/2022. The methodological quality and outcome-specific certainty of evidence were assessed by the AMSTAR 2 and NutriGrade tools, followed by an assessment of the overall certainty of evidence. SRs investigating specific protein sources are described in this review, but not included in the assessment of the overall certainty of evidence. Results Sixteen SRs were considered eligible for the umbrella review. Ten of the SRs investigated total protein intake, six animal protein, six plant protein and four animal vs. plant protein. The majority of the SRs reported no associations or effects of total, animal and plant protein on BP (all “possible” evidence), whereby the uncertainty regarding the effects on BP was particularly high for plant protein. Two SRs addressing milk-derived protein showed a reduction in BP; in contrast, SRs investigating soy protein found no effect on BP. The outcome-specific certainty of evidence of the SRs was mostly rated as low. Discussion/conclusion This umbrella review showed uncertainties whether there are any effects on BP from the intake of total protein, or animal or plant proteins, specifically. Based on data from two SRs with milk protein, it cannot be excluded that certain types of protein could favourably influence BP.

Glycemic response to meals with a high glycemic index differs between morning and evening: a randomized cross-over controlled trial among students with early or late chronotype - Stutz, Bianca; Krueger, Bettina; Goletzke, Janina; Jankovic, Nicole; Alexy, Ute; Herder, Christian; Dierkes, Jutta; Berg-Beckhoff, Gabriele; Jakobsmeyer, Rasmus; Reinsberger, Claus; Buyken, Anette (European Journal of Nutrition)
Abstract Purpose Glycemic response to the same meal depends on daytime and alignment of consumption with the inner clock, which has not been examined by individual chronotype yet. This study examined whether the 2-h postprandial and 24-h glycemic response to a meal with high glycemic index (GI) differ when consumed early or late in the day among students with early or late chronotype. Methods From a screening of 327 students aged 18–25 years, those with early (n = 22) or late (n = 23) chronotype participated in a 7-day randomized controlled cross-over intervention study. After a 3-day observational phase, standardized meals were provided on run-in/washout (days 4 and 6) and intervention (days 5 and 7), on which participants received a high GI meal (GI = 72) in the morning (7 a.m.) or in the evening (8 p.m.). All other meals had a medium GI. Continuous glucose monitoring was used to measure 2-h postprandial and 24-h glycemic responses and their variability. Results Among students with early chronotype 2-h postprandial glucose responses to the high GI meal were higher in the evening than in the morning (iAUC: 234 (± 92) vs. 195 (± 91) (mmol/L) × min, p = 0.042). Likewise, mean and lowest 2-h postprandial glucose values were higher when the high GI meal was consumed in the evening (p < 0.001; p = 0.017). 24-h glycemic responses were similar irrespective of meal time. Participants with late chronotype consuming a high GI meal in the morning or evening showed similar 2-h postprandial (iAUC: 211 (± 110) vs. 207 (± 95) (mmol/L) × min, p = 0.9) and 24-h glycemic responses at both daytimes. Conclusions Diurnal differences in response to a high GI meal are confined to those young adults with early chronotype, whilst those with a late chronotype seem vulnerable to both very early and late high GI meals. Registered at clinicaltrials.gov (NCT04298645; 22/01/2020).

Nutri-Score 2023 update - Merz, Benedikt; Temme, Elisabeth; Alexiou, Hélène; Beulens, Joline Wilhelma Johanna; Buyken, Anette; Bohn, Torsten; Ducrot, Pauline; Falquet, Marie-Noëlle; Solano, Marta García; Haidar, Hanna; Infanger, Esther; Kühnelt, Charlotte; et al. (Nature Food)

Identifying Feedback Types to Augment Feedback Comment Generation - Stahl, Maja; Wachsmuth, Henning (Proceedings of the 16th International Natural Language Generation Conference)
In the context of language learning, feedback comment generation is the task of generating hints or explanatory notes for learner texts that help understand why a part of text is erroneous. This paper presents our approach to the Feedback Comment Generation Shared Task, collocated with the 16th International Natural Language Generation Conference (INLG 2023). The approach augments the generation of feedback comments by a self-supervised identification of feedback types in a multitask-learning setting. Within the shared task, other approaches performed more effective, yet the combined modeling of feedback type classification and feedback comment generation is superior to performing feedback generation only.

On the Universal Transformation of Data-Driven Models to Control Systems - Peitz, Sebastian; Bieker, Katharina (Automatica)
As in almost every other branch of science, the major advances in data science and machine learning have also resulted in significant improvements regarding the modeling and simulation of nonlinear dynamical systems. It is nowadays possible to make accurate medium to long-term predictions of highly complex systems such as the weather, the dynamics within a nuclear fusion reactor, of disease models or the stock market in a very efficient manner. In many cases, predictive methods are advertised to ultimately be useful for control, as the control of high-dimensional nonlinear systems is an engineering grand challenge with huge potential in areas such as clean and efficient energy production, or the development of advanced medical devices. However, the question of how to use a predictive model for control is often left unanswered due to the associated challenges, namely a significantly higher system complexity, the requirement of much larger data sets and an increased and often problem-specific modeling effort. To solve these issues, we present a universal framework (which we call QuaSiModO: Quantization-Simulation-Modeling-Optimization) to transform arbitrary predictive models into control systems and use them for feedback control. The advantages of our approach are a linear increase in data requirements with respect to the control dimension, performance guarantees that rely exclusively on the accuracy of the predictive model, and only little prior knowledge requirements in control theory to solve complex control problems. In particular the latter point is of key importance to enable a large number of researchers and practitioners to exploit the ever increasing capabilities of predictive models for control in a straight-forward and systematic fashion.

Crisis Communication on Twitter: Differences Between User Types in Top Tweets About the 2015 “Refugee Crisis” in Germany - Kapidzic, Sanja; Frey, Felix; Neuberger, Christoph; Stieglitz, Stefan; Mirbabaie, Milad (International Journal of Communication)
The study explores differences between three user types in the top tweets about the 2015 “refugee crisis” in Germany and presents the results of a quantitative content analysis. All tweets with the keyword “Flüchtlinge” posted for a monthlong period following September 13, 2015, the day Germany decided to implement border controls, were collected (N = 763,752). The top 2,495 tweets according to number of retweets were selected for analysis. Differences between news media, public and private actor tweets in topics, tweet characteristics such as tone and opinion expression, links, and specific sentiments toward refugees were analyzed. We found strong differences between the tweets. Public actor tweets were the main source of positive sentiment toward refugees and the main information source on refugee support. News media tweets mostly reflected traditional journalistic norms of impartiality and objectivity, whereas private actor tweets were more diverse in sentiments toward refugees.
Keywords: refugee crisis 2015; Germany; social media; Twitter; user types

Does Augmented Reality Help to Understand Chemical Phenomena during Hands-On Experiments?–Implications for Cognitive Load and Learning - Peeters, Hendrik; Habig, Sebastian; Fechner, Sabine (Multimodal Technologies and Interaction)
Chemical phenomena are only observable on a macroscopic level, whereas they are explained by entities on a non-visible level. Students often demonstrate limited ability to link these different levels. Augmented reality (AR) offers the possibility to increase contiguity by embedding virtual models into hands-on experiments. Therefore, this paper presents a pre- and post-test study investigating how learning and cognitive load are influenced by AR during hands-on experiments. Three comparison groups (AR, animation and filmstrip), with a total of N = 104 German secondary school students, conducted and explained two hands-on experiments. Whereas the AR group was allowed to use an AR app showing virtual models of the processes on the submicroscopic level during the experiments, the two other groups were provided with the same dynamic or static models after experimenting. Results indicate no significant learning gain for the AR group in contrast to the two other groups. The perceived intrinsic cognitive load was higher for the AR group in both experiments as well as the extraneous load in the second experiment. It can be concluded that AR could not unleash its theoretically derived potential in the present study.
Keywords: augmented reality; chemistry education; models; experiment; cognitive load

Experimentelle Kompetenz Physikstudierender - Bauer, Anna Brigitte
Für den Erwerb fachmethodischer Fähigkeiten stellen Laborpraktika eine zentrale Lerngelegenheiten des Physikstudiums dar. Trotz ihrer hohen Bedeutung fehlt ein hochschulfachdidaktischer Diskurs zu einer lehr-lerntheoretischen Fundierung. Zudem wird ihre Lernwirksamkeit aufgrund der bestehenden didaktischen Gestaltung kritisiert. Die weit verbreiteten engmaschigen Aufgabenstellungen enthalten keine Anreize zur tiefergehenden Auseinandersetzung mit den Inhalten. Um der Diskrepanz zwischen den Zielsetzungen und den von den Lernenden erworbenen Fähigkeiten entgegenzuwirken, liegen aktuell nur wenige und zudem nur punktuelle Grundlagen für eine evidenzbasierte Überarbeitung dieses Veranstaltungsformates vor. Ziel dieser Arbeit ist daher, einen Vorschlag für ein performanzorientiertes Kompetenzstrukturmodell auf universitärem Niveau zu entwickeln, das die Inhaltsbereiche, die experimentellen Fähigkeiten und Fertigkeiten sowie die Qualitätsausprägungen experimenteller Handlungen systematisiert.Die Modellierung ist auf Basis der Analyse videografierter experimenteller Performanz von 16 unterschiedlich fähigen Proband:innen realisiert worden. Für die Entwicklung der Dimensionen Fachmethodik und Qualitätsausprägung werden unter Nutzung der qualitativen Forschungsansätze Dokumentarische Methode und Typenbildung die charakteristischen Merkmale universitären Experimentierens identifiziert und anschließend systematisiert. Zur Prüfung der Passung des Modells zur Perspektive der Wissenschaft Physik ist ein Interrating mit einem Fachwissenschaftler durchgeführt worden, das sehr gute Übereinstimmungswerte liefert. Die Passung des Modells zur Perspektive der Praktikumsleiter:innen ist durch ein Expertenrating erfolgt. Ein Rangfolgen-Vergleich zeigt hohe Übereinstimmungswerte.

The association of chronotype and social jet lag with body composition in German students: The role of physical activity behaviour and the impact of the pandemic lockdown - Krueger, Betina; Stutz, Bianca; Jankovic, Nicole; Alexy, Ute; Kilanowski, Anna; Libuda, Lars; Buyken, Anette E. (PLOS ONE)
Young adults with a later chronotype are vulnerable for a discrepancy in sleep rhythm between work- and free days, called social jet lag (SJL). This study analysed (i) chronotype/SJL association with visceral fat/skeletal muscle mass, (ii) the attribution to physical activity behaviour, and (iii) chronotype-specific changes in physical activity behaviour in young adults during the Covid-19 pandemic lockdown. Chronotype and SJL were derived from the Munich-Chrono-Type-Questionnaire in 320 German students (age 18–25 years) from September 2019 to January 2020, 156 of these participated in an online follow-up survey in June 2020. Body composition was assessed by bioimpedance analysis at baseline. Multivariable linear regression analyses were used to relate chronotype/SJL to body composition; the contribution of self-reported physical activity was tested by mediation analysis. At baseline, a later chronotype and a larger SJL were associated with a higher visceral fat mass (P<0.05), this relation was notably mediated by the attention to physical activity (P<0.05). Chronotype (P = 0.02) but not SJL (P = 0.87) was inversely associated with skeletal muscle mass. During the pandemic lockdown, chronotype hardly changed, but SJL was reduced. Timing and physical activity behaviour remained in most participants and changes were unrelated to chronotype (all P>0.07). A later chronotype/higher SJL may increase the risk of a higher visceral fat mass even in this relatively healthy sample, which may be partly due to their physical activity behaviour. Despite a reduction in SJL during the pandemic lockdown, later chronotypes did not change their physical activity behaviour more than earlier chronotypes.
Keywords: Multidisciplinary

Technology education in elementary school using the example of 'learning robots' – development and evaluation of an in-service teacher training concept - Janicki, Nicole; Tenberge, Claudia (Australasian Journal of Technology Education)
Keywords: technology education; teacher professionalisation; Computational Thinking; digitalization; learning robots

Enhancing Comprehension and Navigation in Jupyter Notebooks with Static Analysis - Shivarpatna Venkatesh, Ashwin Prasad; Wang, Jiawei; Li, Li; Bodden, Eric
Jupyter notebooks enable developers to interleave code snippets with rich-text and in-line visualizations. Data scientists use Jupyter notebook as the de-facto standard for creating and sharing machine-learning based solutions, primarily written in Python. Recent studies have demonstrated, however, that a large portion of Jupyter notebooks available on public platforms are undocumented and lacks a narrative structure. This reduces the readability of these notebooks. To address this shortcoming, this paper presents HeaderGen, a novel tool-based approach that automatically annotates code cells with categorical markdown headers based on a taxonomy of machine-learning operations, and classifies and displays function calls according to this taxonomy. For this functionality to be realized, HeaderGen enhances an existing call graph analysis in PyCG. To improve precision, HeaderGen extends PyCG's analysis with support for handling external library code and flow-sensitivity. The former is realized by facilitating the resolution of function return-types. Furthermore, HeaderGen uses type information to perform pattern matching on code syntax to annotate code cells. The evaluation on 15 real-world Jupyter notebooks from Kaggle shows that HeaderGen's underlying call graph analysis yields high accuracy (96.4% precision and 95.9% recall). This is because HeaderGen can resolve return-types of external libraries where existing type inference tools such as pytype (by Google), pyright (by Microsoft), and Jedi fall short. The header generation has a precision of 82.2% and a recall rate of 96.8% with regard to headers created manually by experts. In a user study, HeaderGen helps participants finish comprehension and navigation tasks faster. All participants clearly perceive HeaderGen as useful to their task.
Keywords: static analysis; python; code comprehension; annotation; literate programming; jupyter notebook